Hernando Colón bibliophile and bibliographer. The «Adverte» notes in the Libro de los epítomes - Matilde Malaspina (TECA)
This article discusses a group of handwritten marginal notes of bibliographical content found in the fair copy of the Libro de los epítomes, one of the catalogues and inventories developed by Hernando Colón (1488-1539) for the management of his library. After contextualizing the manuscript and the place of the epítomes within Colón’s knowledge management system, the article describes the features of the six notes and proposes their attribution to Hernando Colón himself. It then offers an examination of the six cases, which deal with uncertain authorships, multiple editions of the same text, incomplete copies, and with a variety of textual contents. The article sheds new light on the content of the collection, on the epitomes intended as a knowledge-management tool and on the processes of their elaboration, as well as on Colón’s interests and involvement in the organization of his library.